1987
DOI: 10.1128/jvi.61.2.239-246.1987
|View full text |Cite
|
Sign up to set email alerts
|

Functional and antigenic domains of the matrix (M1) protein of influenza A virus

Abstract: The membraneand ribonucleocapsid (RNP)-binding domains of the matrix (Ml) protein of influenza A virus (WSN strain) were partially mapped and characterized by reactivity with monoclonal antibodies (MAb) as well as by proteolytic cleavages and amino acid sequencing of the resulting peptides. Of two peptides formed by formic acid hydrolysis, a 9-kilodalton fragment at the amino-terminal third of the Ml protein was recognized by MAb M2-1C6 (to epitope 1), and a 15-kilodalton fragment at the carboxy-terminal two-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 39 publications
3
61
0
Order By: Relevance
“…It is likely that the M1-vRNP complex is formed by the interaction of M1 with the RNA of the vRNP. It has been shown that M1 interacts with the vRNP and inhibits transcription (Watanabe et al, 1996;Ye et al, 1987Ye et al, , 1999. Furthermore, M1 has been shown to bind ssRNA in vitro (Elster et al, 1997) and to vRNP in virusinfected cells (Lopez-Turiso et al, 1990;Ruigrok and Baudin, 1995) and in virus particles (Schulze, 1972), but M1 does not bind to NP expressed alone (Huang et al, 2001;Zhao et al, 1998).…”
Section: Interaction Of M1 With Vrnp and M1 With M1mentioning
confidence: 99%
“…It is likely that the M1-vRNP complex is formed by the interaction of M1 with the RNA of the vRNP. It has been shown that M1 interacts with the vRNP and inhibits transcription (Watanabe et al, 1996;Ye et al, 1987Ye et al, , 1999. Furthermore, M1 has been shown to bind ssRNA in vitro (Elster et al, 1997) and to vRNP in virusinfected cells (Lopez-Turiso et al, 1990;Ruigrok and Baudin, 1995) and in virus particles (Schulze, 1972), but M1 does not bind to NP expressed alone (Huang et al, 2001;Zhao et al, 1998).…”
Section: Interaction Of M1 With Vrnp and M1 With M1mentioning
confidence: 99%
“…C-terminal fragment, aa 165-254) and M1 m (in which the basic residues in the PBD were mutated to alanine residues, 95-AAVALYAALAA-105). Using a similar approach, a qualitative characterization of M1–lipid interaction has previously suggested that the N-terminal domain plays a fundamental role [21], although no consensus was reached regarding the specific regions actually mediating M1–membrane binding [28, 55, 56]. Here, we quantified the binding of the M1 constructs and full-length M1 wt to PS-containing model membranes using a combination of SPR and fluorescence microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…This region is flexible and changes conformation easily under different conditions [Arzt et al, 2004]. A monoclonal antibody against an M1 epitope that resides between amino acids 8 and 89 inhibits reconstitution of the M1 protein with the lipid bilayer, suggesting that this region is the lipid-binding domain of the M1 protein [Ye et al, 1987]. Although the precise mechanisms remain to be clarified, the amino acid change at the position 72 is inferred to influence the nuclear import of the IVpi-189 M1 protein by causing loss of flexibility around the lipid-binding domain, altering the three-dimensional structure of the IVpi-189 M1 protein, and/or the amino acid change alters or decreases the membrane binding activity of the M1 protein.…”
Section: Discussionmentioning
confidence: 99%